Flavonoids activate endothelial nitric oxide synthase by altering their phosphorylation via mitogen-activated protein kinase pathways in glucose-induced endothelial cells. (August 2015) - Kim, Chae Eun; Han, Seongho; Kim, Moo Hyun; Kim, Sung-Whan
Highlights: The two flavonoids naringin and hesperidin increased NO production. The flavonoids increased the HG-induced eNOS expression. HG-induced decrease in eNOS expression is regulated by MAPK pathway. Abstract: Specific mechanisms underlying cardioprotective and anti-inflammatory effects of flavonoids remain unclear. The effects of two flavonoids—hesperidin and naringin—on endothelial nitric oxide synthase (eNOS) induction in human umbilical vein endothelial cells (HUVECs) were investigated here, and possible underlying molecular mechanisms using high glucose (HG) concentrations were examined. The flavonoids' effects on nitric oxide (NO) production and Ser-1177 and Thr-495 phosphorylation with or without mitogen-activated protein kinase (MAPK) signalling pathway inhibitors were determined. HG decreased eNOS mRNA and protein levels while pre-treatment with both flavonoids drastically increased the levels dose- and time-dependently, in HUVECs. Furthermore, HG altered eNOS phosphorylation at Ser 1177 and Thr 495 . Naringin phosphorylated Ser 1177 via the p-38 pathway and dephosphorylated Thr 495 via the mitogen-activated protein kinase kinase (MEK) and c-Jun N-terminal kinase (JNK) pathways. Hesperidin phosphorylated Ser 1177 via the MEK pathway and dephosphorylated Thr 495 via the p-38 and JNK pathways. Thus, hesperidin and naringin regulate HG-induced eNOS expression via the MAPK signalling pathway.